The frequency of Duchenne muscular dystrophy/Becker muscular dystrophy and Pompe disease in children with isolated transaminase elevation: results from the observational VICTORIA study - Kansu, Aydan; Kuloglu, Zarife; Tümgör, Gökhan; Taşkın, Didem Gülcü; Dalgıç, Buket; Çaltepe, Gönül; Demirören, Kaan; Doğan, Güzide; Tuna Kırsaçlıoğlu, Ceyda; Arslan, Duran; Işık, İshak Abdurrahman and Demir, Hülya and Bekem, Özlem and Şahin, Yasin and Bayrak, Nevzat Aykut and Selimoğlu, Mukadder Ayşe and Yavuz, Sibel and Taşkaya, İbrahim Ethem and Altay, Derya and , the VICTORIA Study Group and Taşkın, Didem Gülcü and Bükülmez, Ayşegül and Demir, Arzu Meltem and Tokgöz, Yavuz and Kansu, Aydan and Kuloğlu, Zarife and Kırsaçlıoğlu, Ceyda Tuna and Ayyıldız, Hasret and Kutluk, Günsel and Başaran, Meryem Keçeli and Sezer, Oya Balcı and Özkan, Tanju Başarır and Özgür, Taner and Üstündağ, Gonca Handan and Somuncu, Eda and Tümgör, Gökhan and Yavuz, Sibel and İşlek, Ali and Hoşnut, Ferda Özbay and Şahin, Gülseren Evirgen and Arslan, Duran and Altay, Derya and Doğan, Yaşar and Deveci, Uğur and Dalgıç, Buket and Ceylan, Kamercan and Baştürk, Ahmet and Balamtekin, Necati and Arslan, Melike and Demir, Hülya and Gülşen, Hayriye Hızarcıoğlu and Doğan, Güzide and Comba, Atakan and Selimoğlu, Mukadder Ayşe and Varol, İlknur and; Sebahat and; et al. (Frontiers in Pediatrics, 2023)
Introduction The presence of elevated transaminases and/or creatine phosphokinase can be indicative of underlying muscle disease. Therefore, this study aimed to determine the frequency of Duchenne/Becker muscular dystrophy (DMD/BMD) in male children and the frequency of Pompe disease (PD) in male and female children with isolated hypertransaminasemia. Methods This multi-center, prospective study enrolled patients aged 3-216 months old with serum alanine transaminase [ALT] and/or aspartate transaminase [AST]) >2 x upper limit of normal (ULN) for ≥3 months. Patients with a known history of liver or muscle disease or physical examination findings suggestive of liver disease were excluded. Patients were screened for creatinine phosphokinase (CPK) levels and molecular genetic tests for DMD/BMD in males and enzyme analysis for PD in males and females with elevated CPK levels were performed. PD was confirmed by genetic analysis. Demographic, clinical and laboratory characteristics of the patients were analyzed. Results Overall, 589 patients (66.8% male, mean age 63.4 months (standard deviation 60.5) were included. CPK levels were above ULN in 251 patients (188 male, 63 female). Of the patients assessed, 47% (85/182) of male patients were diagnosed as DMD/BMD and 1% (3/228) of male and female patients were diagnosed as PD. The median ALT, AST and CPK levels were statistically significantly higher and the questioned neurological symptoms and previously un-noticed examination findings were more common in DMD/BMD patients than those without the diagnosis of DMD/BMD or PD (p<0.001). Discussion Questioning neurological symptoms, complete physical examination and testing for CPK levels in patients with isolated hypertransaminasemia will avoid costly and time-consuming investigations for liver diseases and will lead to diagnosing occult neuromuscular diseases. Trial registration: Clinicaltrials.gov NCT04120168